Efforts to Improve Motivation and Learning Outcomes In Mathematics Using Game Methods In Class VI Of Elementary School - Hendriyansyah, Hendriyansyah (Universitas Sebelas Maret, 2022)
The research was motivated by the low motivation and learning outcomes of students at SD Negeri 1 Kerten for the 2021/2022 academic year. Several problems were found. For mathematics lessons, the average score obtained by class VI students on integer operations material, the percentage of students who achieved the standard of learning completeness was 39.58%. This value is very far from the KKM set at SD Negeri 1 Kerten, which is 66%. Based on the research results, it shows that learning using the game method in class VI of SD Negeri 1 Kerten, in Mathematics learning, encourages students to carry out teaching and learning activities well, thereby encouraging students to obtain satisfactory learning achievements.Based on data on student mathematics learning achievement, the class average score in cycle I was 69.62, increasing to 73.51 in cycle II. The percentage of students who achieved the completion standard also increased in cycle I by 88.88% (Good Category), increasing to 100% (Special Category) in cycle II.In this way, the game method can increase the mathematics learning activity and achievement of students at SD Negeri 1 Kerten class VI Semester one of the 2021/2022 academic year.